THE EVALUATION OF WATER QUALITY AND CONSTRUCTION OF WATER PURIFICATION IN KAMPUNG MELAYU SETTLEMENT IN THE EAST OF JAKARTA - M. Syarif Hidayat; Salahuddin Ayup (KOCENIN JURNAL PENGABDIAN KEPADA MASYARAKAT (E) ISSN: 2807-3444, 2022)
Kampung Melayu is an area in East Jakarta that often experiences flooding. Many RWs were affected. One of the impacts is the problem of providing clean water during floods. This community service will discuss the handling of water sources in mosques which are often used as a means of evacuation during floods. In addition, the mosque also functions as a source of clean water when a flood occurs. This Abdimas provides assistance in procuring water tanks for clean water in addition to the existing tanks. The mosque management and the community welcome this activity and it is hoped that there will be other activities in the future